Expression analysis of selected classes of circulating exosomal miRNAs in soccer players as an indicator of adaptation to physical activity - Domanska-Senderowska, D.; Jastrzebski, Z.; Kiszalkiewicz, J.; Brzezianski, M.; Pastuszak-Lewandoska, D.; Radziminki, L.; Brzezianska- Lasota, E.; Jegier, A. (Biology of Sport, 2017)
Recently studies have shown that, depending on the type of training and its duration, the expression levels of selected circulating myomiRNAs (c-miR-27a,b, c-miR-29a,b,c, c-miR-133a) differ and correlate with the physiological indicators of adaptation to physical activity. To analyse the expression of selected classes of miRNAs in soccer players during different periods of their training cycle. The study involved 22 soccer players aged 17-18 years. The multi-stage 20-m shuttle run test was used to estimate VO2 max among the soccer players. Samples serum were collected at baseline (time point I), after one week (time point II), and after 2 months of training (time point III). The analysis of the relative quantification (RQ) level of three exosomal myomiRNAs, c-miRNA-27b, c-miR-29a, and c-miR-133, was performed by quantitative polymerase chain reaction (qPCR) at three time points - before the training, after 1 week of training and after the completion of two months of competition season training. The expression analysis showed low expression levels (according to references) of all evaluated myomiRNAs before the training cycle. Analysis performed after a week of the training cycle and after completion of the entire training cycle showed elevated expression of all tested myomiRNAs. Statistical analysis revealed significant differences between the first and the second time point in soccer players for c-miR-